Relationships of Physical Activity and Diet Quality with Body Composition and Fat Distribution in US Adults. Issue 12 (24th October 2020) - Xu, Furong; Greene, Geoffrey W.; Earp, Jacob E.; Adami, Alessandra; Delmonico, Matthew J.; Lofgren, Ingrid E.; Greaney, Mary L.
Abstract : Objective: This study aimed to investigate the relationships among physical activity (PA), diet quality, body composition, and fat distribution in a representative sample of US adults. Methods: A cross‐sectional analysis was conducted using publicly accessible data from the 2011 to 2016 National Health and Nutrition Examination Survey and the Food Patterns Equivalents Database ( n = 7, 423). Variables from the data sets were analyzed for this study, including PA, two 24‐hour dietary recalls, and dual‐energy x‐ray absorptiometry outputs. Results: For men, PA and diet quality were inversely associated with the percentage of body fat (β = −0.0042, 95% CI: −0.0084 to −0.0001; β = −0.28, 95% CI: −0.42 to −0.14) and fat mass index (β = −0.0125, 95% CI: −0.0209 to −0.0041; β = −0.56, 95% CI: −0.81 to −0.32); meeting the PA recommendation and having good diet quality provided an additive effect on body fat. A similar pattern was observed in women. Additionally, diet quality was inversely associated with all fat distribution measures in both sexes, whereas PA was positively associated with lean mass measures in men only. Conclusions: Increased PA and/or better diet quality were associated with reduced body fat, a healthier fat distribution, and increased lean mass. Further research examining how changes in PA or diet quality influence body composition and fat distribution in adults is warranted.